Calculation of the electromagnetic scattering by non-spherical particles based on the volume integral equation in the spherical wave function basis. (July 2019) - Shcherbakov, Alexey A.
Highlights: The Generalized Source Method is used to develop T-matrix calculation methods: scattering matrix and scattering vector algorithms. Scattering matrix algorithm provide a new recurrence for T-matrix calculation. Scattering vector algorithm is highly parallelizable and yields accurate power balance. A method for consideration of arbitrary polyhedral particles is suggested. Abstract: The paper presents a scattering matrix and scattering vector methods for calculation of non-spherical particle T-matrices, which are based on the volume integral equation and the spherical vector wave function basis, and rely on the Generalized Source Method rationale. The derivation of the scattering matrix method is based on ideas previously used within the matrix operator method of the radiative transfer theory and the S-matrix method of the grating diffraction theory, and provides a new T-matrix recurrence relation being alternative to the recurrences used within the Invariant Imbedding and the Superposition T-matrix methods. The developed scattering vector algorithm for calculation of T-matrix single columns is shown to have a potential for parallelization and to yield an almost zero power balance for purely dielectric particles. Demonstrated results of electromagnetic scattering simulations include examples for spheroids and a complex non-symmetric polyhedron particle.